Effect of Met/Leu substitutions on the stability of NAD plus -dependent formate dehydrogenases from Gossypium hirsutum - Kurt, Sinem; Ordu, Emel (Springer, 2021)
NAD(+)-dependent formate dehydrogenases (FDHs) are extensively used in the regeneration of NAD(P)H and the reduction of CO2 to formate. In addition to their industrial importance, FDHs also play a crucial role in the maintenance of a reducing environment to combat oxidative stress in plants. Therefore, it is important to investigate the response of NAD(+)-dependent FDH against both temperature and H2O2, to understand the defense mechanisms, and to increase its stability under oxidative stress conditions. In the present study, we characterized the oxidative and thermal stability of NAD(+)-dependent FDH isolated from cotton, Gossypium hirsutum (GhFDH), by investigating the effect of Met/Leu substitutions in the positions of 225, 234, and 243. Results showed that the single mutant, M234L (0.72 s(-1) mM(-1)), and the triple mutant, M225L/M234L/M243L (0.55 s(-1) mM(-1)), have higher catalytic efficiency than the native enzyme. Substitution of methionine by leucine on the position of 243 increased the free energy gain by 670 J mol(-1). The most remarkable results in chemical stability were seen for double and triple mutants, cumulatively. Double and triple substitution of Met to Leu (M225L/M243L and M225L/M243L/M234L) reduce the k(in)(ef) by a factor of 2 (12.3x10(-5) and 12.8x10(-5) s(-1), respectively.
Keywords: Thermal stability; Oxidative stability; Cumulative mutation effect; Methionine